RELASI AGAMA DAN POLITIK (Kajian relasi Islam dan politikdalam berbagai dimensi) - Atnawi Atnawi (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2018)
Islam is a religion revealed by Allah swt as guidance for mankind in performing duties as creatures and kholifah of Allah SWT, is tasked to preserve and maintain the regulation of life, it means the regulation and life cycle are balance in social and vertical relation. While on the other side, there isa political term which is regulates the issue of social relations between humans and others, in order to maintain and achieve interests. Islam is as a religion that has a teaching and rules of a life, namely the Qur'an, is as a guide of life of Muslims, then the political issue (syiasah) has been arranged too. Thus, the questionis,the relationship between politics and religion is closely intertwined and intersect. But in practice in the field, there are some problems that have some interpretations differently,it separates the affairs of the world with the matter of the afterlife, which is to separate the affairs of politics and Religion. This happens because the political aspect is considered government power that it is not suitable with the Religion aim, such as, the loss of value of honesty, the thinness of the sense of brotherhood, and that there is the interests that it is became the main goal in politics.